RE-EXAMINING THE EXISTENCE OF LOW PRICE-EARNINGS RATIO EFFECTS: A Descriptive Approach to the Case of Indonesian Stock Market - Marwan Asri (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
From practical point of view, Price-Earnings (P/E) ratio is one of numerous important aspects to consider. Analysts, investors, and traders in stock markets use P/E ratio –together with other information- in analyzing the past performance, and predicting the future prospect of securities in the market. However, noting its importance, there are some significant disagreements among researchers regarding the ability of P/E ratio in providing “correct information” about the future return of company stocks. One of the topics under discussion is about the presence of so-called low P/E effect, which hypothesizes that high P/E will be followed by low returns and low P/E will be followed by high returns. This study, by repeating partially Johnson et al. (1989) procedures, was trying to confirm the low P/E effect hypothesis in Indonesian market. The study involved 267 stocks listed in Jakarta Stock Exchange in the sample frame and selected the period of 1994-2000 as the focus of analysis. The study also has an intention to investigate whether there was a structural change in return-P/E relationship from the pre-crisis period (1994-1996) to the crisis period (1998-2000). The procedure of analysis was divided into two sections. In the first section a descriptive macro (market) analysis was presented, to test the hypothesis at the market level. It started with an overview about the fluctuation and trend of market P/E ratios during the period of 1991-2000, and followed by investigating the relationship between market P/E and the following returns. A regression analysis was also performed to strengthen the analysis from statistical point of view. In the second section, analysis is more directed to the portfolio level where the portfolios were ranked according to their P/E ratios. The study was concluded with a main finding that does not support the low P/E effect hypothesis.